Voluntary versus involuntary telecommuting and employee innovative behaviour: a daily diary study - Huo, Weiwei; Gong, Jingya; Xing, Lu; Tam, Kwok Leung; Kuai, Hejing (International journal of human resource management, 2023)
During the COVID-19 crisis, telecommuting has gradually attracted the public's attention. Past studies on the subject have produced inconsistent findings, suggesting that telecommuting can lead to simultaneous benefits and drawbacks. To discuss the deeper reasons for this finding, we divided telecommuting into two types-voluntary and involuntary telecommuting. Based on the job demands-resources model, we explored the impact of voluntary-involuntary telecommuting on employee innovative behaviour through co-worker emotional support, and we examined the cross-level moderating effect of organisational identification. Using the daily diary method, we collected 455 valid observations from 65 employees for eight consecutive days. The results show that compared with involuntary telecommuting, voluntary telecommuting leads to more co-worker emotional support, in a mediating role, and employee innovative behaviour. Furthermore, a high level of organisational identification enlarges the difference in co-worker emotional support for employees voluntarily or involuntarily telecommuting. Our results uncover those differences and fill the research gap on telecommuter motivation.